Mechanistic insights to drive catalytic hydrogenation of formamide intermediates to methanol via deaminative hydrogenation - Kothandaraman, Jotheeswari; Heldebrant, David J.; Lopez, Johnny Saavedra; Dagle, Robert A. (Frontiers in Energy Research, 2023)
Amine-promoted hydrogenation of CO2 to methanol typically proceeds via a formamide intermediate when amines are used as additives or if the hydrogenation is performed in carbon capture solvents. The catalysts used for the hydrogenation of the formamide intermediate dictate the selectivity of the products formed: 1) Deoxygenative hydrogenation (C-O bond cleavage) resulting in N-methylation of amine and deactivation of the solvent, 2) Deaminative hydrogenation (C-N bond cleavage) resulting in formation of methanol and regeneration of the solvent. To date, catalytic reductions of CO2 with amine promoters suffer from poor selectively for methanol which we attribute to the limiting formamide intermediate, though to date, the conditions that favor C-N cleavage have yet to be fully understood. To better understand the reactivity of the formamide intermediates, a range of heterogenous catalysts were used to study the hydrogenation of formamide. Well-known gas phase CO2 hydrogenation catalysts catalyze the hydrogenation of formamide to N-methyl product via C-O bond cleavage. However, the selectivity can be readily shifted to selective C-N bond cleavage by addition of an additive with sufficient basicity for both homogenous and heterogeneous catalytic systems. The base additive shifts the selectivity by deprotonating a hemiaminal intermediate formed in situ during the formamide hydrogenation. This prevents dehydration process leading to Nmethylated product, which is a key capture solvent deactivation pathway that hinders amine use in carbon capture, utilization, and storage (CCUS). The findings from this study provide a roadmap on how to improve the selectivity of known heterogenous catalysts, enabling catalytic reduction of captured CO2 to methanol.